Reliable epileptic seizure detection using an improved wavelet neural network - Zainuddin, Zarita; Lai, Kee Huong; Pauline, Ong (The Australasian Medical Journal Pty. Ltd, 2013)
Electroencephalogram (EEG) signal analysis is indispensable in epilepsy diagnosis as it offers valuable insights for locating the abnormal distortions in the brain wave. However, visual interpretation of the massive amounts of EEG signals is time-consuming, and there is often inconsistent judgment between experts.